Catheter-related bloodstream infection associated with multiple insertions of the peripherally inserted central catheter in patients with hematological disorders - Yoshinori Hashimoto (Nature Portfolio, 2021)
Abstract Patients with hematological disorders are treated with multiple cycles of chemotherapy. As a result, they often require multiple insertions of the peripherally inserted central catheter (PICC) for prolonged periods of time. Although PICCs have been widely used worldwide in various patients, the safety and feasibility of the multiple insertions of the PICC in this population have not been fully verified. We performed a retrospective analysis to clarify the relationship between complications and multiple PICC insertions in patients with hematological disorders who were treated with either chemotherapy or immunotherapy. A total of 651 PICCs were inserted in 261 patients with a median age of 66 years. Acute myeloid leukemia (AML) and non-Hodgkin's lymphoma were the most common diseases in our patient cohort. The total catheter days (CDs) was 29,485 days, with a median catheter duration of 30 days. The rate of catheter-related bloodstream infection (CRBSI) in our patient cohort at high rate of re-insertion was 2.0/1000 CDs. Although multiple PICC insertions were not a risk factor of CRBSI, our findings suggest that a prolonged catheter dwell time may be associated with CRBSI. AML was an important risk factor of CRBSI. While the PICC dwell time depends on the treatment cycle, our findings indicate that it should be limited to approximately 30 days and catheters may be removed and re-inserted as needed.